Digital image analysis technologies for decision support systems in agricultural - Mingxin Huang; Vatskel, Vladimir (КНУБА, 2019)
The paper describes information technologies for efficient management of crop yields and decision-making support in agriculture as a whole. The analysis of automation technologies supporting decision-making in agriculture indicates the necessity of their improvement and integration of new functions for increasing the yield and quality of agricultural products, increasing the efficiency of operational management of sown areas. The paper formulates the research tasks arising from the review of geoinformation technologies and technologies for the analysis of digital images of sown areas.
Keywords: geoinformation technologies; agriculture; decision-making support; 338.33; 338.43:005.8